Consumer Engagement through Experiential Marketing: A Case Study of Kopi Chuseyo in Depok - Sulastri, Nurfadillah; Fadillah, Adil (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Business creates goods or services using experiential marketing strategies, engaging the consumer’s five senses, heart, and mind. If a product successfully triggers consumers’ emotions, they might consider it an unforgettable experience. A memorable experience is when customers undergo a pleasurable event that they can recall, leading to customer satisfaction as their expectations align with what’s delivered. This has a significantly positive impact on businesses as happy customers are more inclined to recommend the business’s goods and services to others. The purpose of this discussion is to Understand the application of experiential marketing at Kopi Chuseyo, Identify the constraints in applying experiential marketing at Kopi Chuseyo, and Recognize methods to address the constraints in applying experiential marketing at Kopi Chuseyo. The implementation of experiential marketing at Kopi Chuseyo in Depok has been successful in attracting many customers and complies with the five factors of experiential marketing: sense, feel, think, act, and relate. Kopi Chuseyo in Depok creates diverse and engaging events that boost consumer purchasing interest. However, in implementing experiential marketing, Kopi Chuseyo in Depok faces some limitations: limited venue capacity, available facilities, and event merchandise. Efforts to resolve these issues in implementing experiential marketing at Kopi Chuseyo in Depok include expanding venue capacity, increasing facilities, and augmenting event merchandise supplies.